The influence of physical education courses integrated with civic education on prosocial behavior among college students: the chain mediating effect of cultural confidence and self-esteem - Huang, Changchang; Li, Geng; Zhang, Yuantong; Aphichaithawon, Nalatporn; Deng, Zhile; Zhang, Zhihua; Zhang, Yihan; Ding, Jianjun (Frontiers in Psychology, 2023)
Objective: This study sought to uncover the relationship between Physical Education Courses Integrated with Civic Education (PECICE) and prosocial behavior among university students.Additionally, we aimed to decipher the mediating roles of cultural confidence and self-esteem within this relationship.Methods: Employing a questionnaire-based approach, we assessed the relationship among PECICE, cultural confidence, self-esteem, and prosocial behavior in university students. The instrument comprised four distinct scales: the Perceived Effectiveness Scale for PECICE, the Cultural Confidence Scale, the Self-Esteem Scale, and the Prosocial Behavior Scale. Our sample encompassed 293 Chinese college students, consisting of 137 men and 156 women, with an average age of 21.39 years (SD = 2.1).Results: PECICE demonstrated significant positive associations with cultural confidence (r = 0.29, p < 0.001), self-esteem (r = 0.35, p < 0.001), and prosocial behavior (r = 0.40, p < 0.001). The influence of PECICE on prosocial behavior among university students was mediated through three channels: solely via cultural confidence (mediating effect value: 0.14), solely via self-esteem (mediating effect value: 0.22), and through the combined influence of both cultural confidence and self-esteem (mediating effect value: 0.2).2 Conclusion: The intertwined mediating roles of cultural confidence and self-esteem highlight their pivotal significance in enhancing the efficacy of PECICE. These insights offer a valuable reference for both educators and policymakers striving to augment prosocial behavior in university students.